The relationship of height, weight and body mass index with curvature of spine kyphosis and lordosis in 12-15-year old male adolescents of Tehran - Alireza Rabıeezadeh; Fariborz Hovanloo; Mehdi Khaleghı; Hadi Akbarı (Türk Spor ve Egzersiz Dergisi)
Normal curvature of the spine might be changed as a result of its non-fixed feature. The aim of this study was to investigate the relationship between height, weight and body mass index (BMI) with curvature of the spine kyphosis and lordosis in 12-15year-old male adolescents of Tehran. This was a correlational study in which 97 accessible healthy boy students from Tehran region 2 (13.8 ± 0.8 years old) participate were selected. After measuring height (157.4 ± 8.6 cm), weight (52.9 ± 11.9 kg) and calculating BMI (21.2 ± 3.9 kg/m2), the spinal mouse was used to spinal assessment. To investigate the relationship between study variables Pearson correlation coefficient was used. The results of Pearson correlation coefficient showed there was no statistically significant relationship between study variables including height and kyphosis curvature (r= -0.047, p= 0.651), height and lordosis curvature (r= -0.026, r= 0.800), weight and kyphosis curvature (r= 0.015, p= 0.883), weight and lordosis curvature (r= 0.052, p= 0.610), body mass index and kyphosis curvature (r= 0.059, p= 0.566), and body mass index with lordosis curvature (r= 0.084, p= 0.413). Therefore, although it seems that anomalies of the spine have high prevalence among the students, the results of this study showed that height, weight and body mass index could not be considered as an appropriate criterion to associate of kyphosis and lordosis angles in the studied population.